Effect of Famciclovir on Herpes Simplex Virus Type 1 Corneal Disease and Establishment of Latency in Rabbits - Loutsch, Jeannette M. (American Society for Microbiology, 2001)
Famciclovir (FCV) is efficacious in the treatment of acute herpes zoster and recurrent genital infections but has not been used to treat ocular herpes simplex virus (HSV) infections. We evaluated the efficacy of orally administered FCV in treating HSV-1 epithelial keratitis and determined its effects on the establishment of latency and subsequent reactivation. Rabbits were inoculated with HSV-1 strain 17 syn+ and treated twice daily with increasing concentrations of FCV (60 to 500 mg/kg of body weight). This resulted in a significant, dose-dependent improvement in keratitis scores, as well as prolonged survival. Regardless of the dose of drug used, all groups exhibited the high rates of spontaneous and induced reactivation characteristic of 17syn+. The efficacy of 250 mg of FCV per kg was also compared to topical treatment with 1% trifluorothymidine (TFT). Although TFT treatment was more effective at reducing eye disease, FCV-treated rabbits had a better survival rate. Real-time quantitative PCR analysis of rabbit trigeminal ganglia (TG) demonstrated that FCV significantly reduced the HSV-1 copy number compared to that after treatment with TFT or the placebo but not in a dose-dependent manner. In summary, oral FCV treatment significantly reduces the severity of corneal lesions, reduces the number of HSV-1 genomes in the TG, improves survival, and therefore may be beneficial in reducing the morbidity of HSV keratitis in the clinic.